Answer:
a) [tex](-\frac{\sqrt{24}}{6} ,\frac{\sqrt{24}}{12} ,-\frac{\sqrt{24}}{12})[/tex]
b) [tex](-1,1,2)[/tex]
c) [tex]-2x+y-z=1[/tex]
Step-by-step explanation:
a)
AB, OB, OA are vectors.
[tex]AB = OB - OA = (-3, 2, 1) - (1, 0, 3) = (-4, 2, -2)\\||AB|| = \sqrt{(-4)^2+2^2+(-2)^2}=\sqrt{24}\\[/tex]
Normalizing AB: [tex]\frac{AB}{||AB||} = (\frac{-4}{\sqrt{24}},\frac{2}{\sqrt{24}}, \frac{-2}{\sqrt{24}})=(-\frac{\sqrt{24}}{6} ,\frac{\sqrt{24}}{12} ,-\frac{\sqrt{24}}{12})[/tex]
b)
OM, OA, OB are vectors.
[tex]OM = \frac{1}{2}OA+\frac{1}{2}OB=(\frac{-3+1}{2} ,\frac{2+0}{2}, \frac{1+3}{2} )=(-1,1,2)[/tex]
So, [tex]M = (-1,1,2)[/tex]
c)
[tex]-4x+2y-2z=(-4)(-1)+(2)(1)+(-2)(2)=4+2-4=2[/tex]
Hence,
[tex]-2x+y-z=1[/tex]